IN SILICO STUDY OF MONOSACCHARIDE COMPOUNDS EFFECT ON B CELL RECEPTORS (BCR) FROM NONI FRUIT (MORINDA CITRIFOLIA) - ANWAR, LA ODE MUHAMMAD; RUMIYATI; SASMITO, EDIATI (International Journal of Current Pharmaceutical Research, 2019)
Objective: Noni fruit has been widely used as a treatment. The content of saccharides in noni can affect the immune system, especially as independent antigens (TI) against B cell receptors (BCR). TI can produce antibodies without being influenced by T cells. Therefore, this study aims to look at the effect of IT on BCR with the in silico method approach. Methods: Ligands were obtained from Zink Web and macromolecules were obtained from Protein Data Bank with code 2H32. Ligand optimization using VegaZZ software and macromolecules is optimized using UCSF Chimera software. Ligands and macromolecules are docking using MOE software. Result: The results showed that monosaccharide compounds have an interaction with BCR, which is characterized by a decrease in free energy. The D-Galactose compound has the largest binding affinity of-4.80 kcal/mol. Conclusion: Monosaccharide compounds are independent antigens (TI) of noni (Morinda citrifolia) that can affect on B cell receptors (BCR), which have identical epitopes.